Pengaruh Good Corporate Governance dan Whistleblowing System Terhadap Kecurangan di Perusahaan Perbankan yang Terdaftar di BEI Periode 2021-2023 - Stephanie, Putri; M, Martin; Basri, Cecilia Almeira; Magaretha, Agrade (Madani: Jurnal Ilmiah Multidisiplin, 2024)
In banking companies, it is never separated from fraud cases, this fraud certainly makes the name of the banking company tarnished, causing losses to the company. According to a survey from the Association of Certified Fraud Examiners (ACFE) in 2022, Indonesia is the country that has the 4th highest number of cases of fraud in Pacific Asia where the cases committed are dominated by acts of corruption, misuse of assets and fraud on financial statements. For this reason, the existence of a Whistleblowing System and Good Corporate Governance is considered to be able to overcome the acts of fraud that occur. The data analysis technique used in this research is multiple linear regression analysis. This data collection uses purposive sampling so that 27 companies listed on the Indonesia Stock Exchange are obtained within a one-year period.